Narrative Learning in the Adult Classroom - M. Carolyn Clark; Marsha Rossiter (Adult Education Research Conference, 2008)
Narrative is a fundamentally human way of making meaning. In this study we explore how narrative can be used to foster learning in higher education and how it provides a way to conceptualize the learning process itself. To do this we examine the use of autobiographical learning portfolios in a nontraditional undergraduate program and the use of learning journals in a graduate course in adult education.
Keywords: narrative learning; autobiographical portfolios; learning journals